Ocular complications of tamoxifen: case report and literature review - Hyży-Topolewska, Anna; Wojtacki, Janusz; Leśniewski-Kmak, Krzysztof; Różycki, Radosław (Contemporary Oncology/Współczesna Onkologia, 2003)
Tamoxifen is a synthetic antiestogen used as endocrine therapy in women with estrogen and/or progesterone-receptor positive breast cancers, despite the stage of the disease and age as well, both as a treatment for advanced cancer and in adjuvant setting; its potential use as a chemopreventive agent is currently under investigation. As more than thirty-years of experience show, tamoxifen is a well tolerated and safe drug and its side effects are usually moderate and transient (hot flashes, vaginal discharge, headache, and, rarely, nausea and skin rashes). Ocular toxicity is rather rare tamoxifen-related complication: the incidence reported in retrospective studies ranges from 0 to 23.5%, depending on the daily and cumulative tamoxifen dose and the methodology of the study. Tamoxifen may destroy almost each part of the visual system, but retinopathy as well keratopathy (usually asymptomatic) are relatively characteristic, whereas optic neuritis is relatively rare. The study reports a case of 48-year-old breast cancer women (pT2pN0M0, grade II according to Bloom-Richarson criteria, positive staining for estrogen and progesterone receptors), who experienced reversible decreased bilateral visual acuity with retinopathy after six months of adjuvant therapy (daily dose: 20 mg/d., cumulative dose: 3.7 g). Other reasons of visual disturbances were excluded due to the precise medical history and differential diagnostic procedures. Following 4 weeks of tamoxifen discontinuation all visual symptoms regressed as well as the changes observed at the fundus of the eye. The current literature on the topic is reviewed and discussed, particularly in relation to epidemiology, risk factors, clinical course, differential diagnosis and screening guidelines of the complication.